(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: The study examines some morphological and histological factors that may contribute to condylar cartilage (CC) formation. The specimens used were consecutive sections obtained from 20 human fetuses ranging in age from 10 to 15 weeks. The vascular canals (VC) emerge in the CC and initiate the process of intramembranous ossification. The mandibular condylar cartilage is crucial for the growth and function of the mandible, and it also contributes to the development of the Temporomandibular joint. Understanding the development of mandibular condylar cartilage throughout the early stages of gestation is essential for detecting congenital craniofacial deformities. Objectives Examine the stages of MCC development in human samples from fetuses at 10-15 weeks of gestation. Study Design: A descriptive Cross-sectional Study. Place and Duration of Study: Department of Anatomy and Obstetric Nowshera Medical College from 15th Nov 2020 to 1st Jun 2021. The changes in the shape and size of the bones and the processes of bone formation should also be determined. Methods: The current study is descriptive, cross-sectional, and involves post-mortem human fetal specimens aged 10-15 weeks. The specimens were obtained from the Department of Obstetrics of QHAMC after miscarriages and intrauterine deaths. The absence of external and congenital malformations was verified. Light microscopic and histological assessment was done with the aid of H&E-stained sections. Results Twenty fetal specimens were used in the study, with an average gestation period of 12. 5 weeks (±1. 5 weeks). Histological analysis revealed gradual chondrocyte maturation and the beginning of the ossification process. At ten weeks, MCC was comprised of undifferentiated mesenchymal cells. At twelve weeks, it is possible to observe the differentiation of chondrocytes and early ossification. At 15 weeks, the ossification stages of the CRL were at a superior level with the hypertrophic chondrocytes and mineralized cartilage. The p-values for differences in developmental stages between the gestational ages were less than 0. Hence, the differences were statistically significant. Conclusion The MCC in human specimens at 10–15 weeks' gestation undergoes considerable morphological transformation and commences the ossification process. Knowledge of these stages is essential in identifying and intervening in congenital craniofacial disorders. The authors recommend that future studies focus on investigating molecular processes that may contribute to the development of MCC.